The vintage book of ghosts - Uglow,Jenny (Vintage, 1994)
An anthology that gathers together the literature of ghosts - stories, poems, newspaper extracts and filmscripts - ranging in source from the Bible and Norse sagas to the works of contemporary writers such as Seamus Heaney and Angela Carter